Refleksi Sikap Pembimbing Kemasyarakatan Terhadap Klien Pemasyarakatan di Balai Pemasyarakatan Kelas I Palangka Raya - Rizkiana Rizkiana; Arini Safitri; Gerry Olvina Faz; Antoni Lugas Pambudi (Institut Agama Islam Negeri Curup, 2022)
The purpose of this study was to determine the attitude of the correctional advisor towards correctional clients at the Bapas Kelas I in Palangka Raya. For this type of research, the research method used is a qualitative method which seeks to describe the actual situation in the field where the observations were made. Sources of data obtained from interviews and observations of five informants who are correctional advisors with certain age criteria and the work experience of the informants while serving as correctional advisor. From these data sources, it was found that the attitude of the correctional advisor towards the correctional client refers to attitude indicators such as the cognitive aspect, namely the assessment of the correctional advisor to the correctional client is an individual who is lost and is having problems so that in the end they had to deal with the law. In the affective aspect, it is implemented into various emotions such as sad, happy, angry, etc., these emotions arise after the correctional advisor carries out guidance with the correctional client. Then the cognitive aspect is implemented into action resulting in the attitude of the correctional advisor when helping the problem solving process of the correctional client.